2020
DOI: 10.1201/9781003046981
|View full text |Cite
|
Sign up to set email alerts
|

The use of Delft3D to simulate the deposition of cohesive and non-cohesive sediments in irrigation systems

Abstract: There are many people who were involved and gave lots of assistance and cooperation in this research. The author would like to deliver the gratefulness for their contribution. Firstly, I would like to thank my Promoter and supervisor, Prof. Charlotte de Fraiture PhD, MSc who gave opportunity, ideas and support to this study, also I would like to thank Dr. Bert Jagers from Deltares for always sharing the ideas, knowledge and encouragement, the technical support and guiding me during this research and for his ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…The study confirms that gate operations have a significant impact on the overall hydrodynamic and morphologic behavior of the irrigation system [43]. The simulations using a multi-dimensional numerical showed that opening the gate on the side of offtake resulted in less deposition of sediment at the entrance of the offtake than when the gate on the other side of the offtake was opened.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The study confirms that gate operations have a significant impact on the overall hydrodynamic and morphologic behavior of the irrigation system [43]. The simulations using a multi-dimensional numerical showed that opening the gate on the side of offtake resulted in less deposition of sediment at the entrance of the offtake than when the gate on the other side of the offtake was opened.…”
Section: Discussionsupporting
confidence: 68%
“…While the 3D mode provides a slightly better description of the physics involved, the running times are quite long for large irrigation canal networks. Compared to 1D models, the use of Delft3D run in 2D mode has a clear benefit by providing an estimate of the asymmetric development of the hydraulics and morphology, while avoiding the long simulation times of 3D models [43]. However, for the simulations considered here the extra simulation time of the 3D models has not shown a significant benefit for this type of application.…”
Section: Discussionmentioning
confidence: 99%
“…Sediments can be classified into cohesive and non-cohesive. Cohesive sediments are composed primarily of clay-sized material with strong inter-particle forces due to their surface ionic charge and are usually found flocculated in suspension mode (Theol, 2020). On the other hand, non-cohesive sediments are composed primarily of sand material with weak interparticle forces (Theol, 2020).…”
Section: Numerical Modelmentioning
confidence: 99%
“…Cohesive sediments are composed primarily of clay-sized material with strong inter-particle forces due to their surface ionic charge and are usually found flocculated in suspension mode (Theol, 2020). On the other hand, non-cohesive sediments are composed primarily of sand material with weak interparticle forces (Theol, 2020). They are usually transported by bedload and suspended load during tsunamis (e.g., Sugawara et al, 2014).…”
Section: Numerical Modelmentioning
confidence: 99%